Helium-isotope constraints on palaeoceanographic change and sedimentation rates during precession cycles (Cenomanian Scaglia Bianca Formation, central Italy) - Lucas, JR; Batenburg, SJ; Hillegonds, DJ; Mabry, JC; Jenkyns, HC; Ballentine, CJ; Robinson, SA (Wiley, 2024)
For much of the pelagic sedimentary record, time control is limited to the resolution of precession cycles (ca 20 kyr): the Milankovitch parameter that forms the most detailed metronome for the Cenozoic and Mesozoic Eras. The influence of precession is often detected in lithological alternations, where the duration represented by individual lithologies is not well constrained. Here the novel technique of extraterrestrial helium abundance (3HeET) is used to investigate the sedimentation dynamics and palaeoceanography within individual precessional cycles. High-resolution 3HeET timescales were produced for four precession cycles from the rhythmically bedded Scaglia Bianca Formation, a sequence of Upper Cretaceous (Cenomanian) deep-marine pelagic limestones from central Italy that are well characterized by cyclostratigraphy. Using 3HeET concentrations as a proxy for sedimentation rate allows instantaneous sedimentation rates and organic-carbon mass accumulation rates to be calculated for each bed within a precession cycle. Eccentricity is known to modulate the amplitude of precession forcing, and precession cycles deposited under eccentricity maxima and minima were selected for comparison. Lithological changes through these chert–(black shale)–limestone cycles are explained using the concept of ‘palaeoenvironmental thresholds’; these timescale calculations indicate that when the amplitude of precessional insolation forcing was greatest (at eccentricity maxima) the palaeoenvironmental system spent longer in the more nutrient-rich environment under which siliceous and organic-rich sediments were deposited, reflecting increased time spent above a ‘threshold’ insolation level. Estimates of primary productivity are relatively elevated for organic-rich beds. An increase in the flux of terrestrial helium (4Heterr) during the deposition of cherts may have been coincident with an increase in terrestrially derived nutrients. The presented results indicate great potential for the use of 3HeET to understand past oceanographic, climatic and sedimentological processes at high temporal resolution.